Producción simple y conjunta a consecuencia de Sraffa - Mora Plaza, Antonio (Nómadas. Critical Journal of Social and Juridical Science, 2010)
The joint production is an historical matter from Sraffa, although the text books don´t treat it frequently, perhaps for the formal accommodation to the single production, despite that the joint production is the question more empirical important. Along this papers will appear the names of authors who they have treated this question under a ricardian or neo-ricardian survey. The marginalist joint production is obviated. The other hand, is not my intention to talk about the the historical developement of joint production. This matter has been worked with succes and facilitated many graduates and doctorates. This is an attempt to contribute with somes ideas and to make also somes criticals to the unquestioned knowledge.